Religion-Based Character Building: Islamic Education Strategies for Children with Disabilities at SLBN 31 Pangkal Pinang - Shinta Lestari Oktarini; Feni Yulianti (Universitas Negeri Padang, 2025)
The Islamic education learning strategy for students with disabilities at SLBN 31 PKLK Pangkal Pinang is basically carried out in accordance with general provisions, but there are significant differences related to the conditions of students who have different levels of intellectual and social intelligence compared to children of the same age in general. The objective of this study is to analyze the Islamic education learning strategies and supporting factors and obstacles in character building for students with disabilities at SLBN 31 PKLK Pangkal Pinang. The researcher conducted qualitative field research by collecting data through interviews, observations, and supporting documentation, and analyzing it using the Spradley model. The researcher found that Islamic religious education strategies in character building include expository, cooperative, and contextual learning strategies that shape the character of students with disabilities to be pious, independent, and polite. The success of character building is also supported by competent Islamic Religious Education teachers and supportive parents. However, there are obstacles in the character-building process, such as student factors, the environment, the Islamic Religious Education teachers themselves, and the curriculum.